A review of bring your own device on security issues - Olalere, Morufu; Abdullah, Mohd Taufik; Mahmod, Ramlan; Abdullah, Azizol (SAGE Publications, 2015)
Mobile computing has supplanted internet computing because of the proliferation of cloud-based applications and mobile devices (such as smartphones, palmtops, and tablets). As a result of this, workers bring their mobile devices to the workplace and use them for enterprise work. The policy of allowing the employees to work with their own personal mobile devices is called Bring Your Own Devices (BYOD). In this article, we discuss BYOD’s background, prevalence, benefits, challenges, and possible security attacks. We then review contributions of academic researchers on BYOD. The Universiti Putra Malaysia online databases (such as IEEE Xplore digital library, Elsevier, Springer, ACM digital library) were used to search for peer-reviewed academic publications and other relevant publications on BYOD. The Google Scholar search engine was also used. Our thorough review shows that security issues comprise the most significant challenge confronting BYOD policy and that very little has been done to tackle this security challenge. It is our hope that this review will provide a theoretical background for future research and enable researchers to identify researchable areas of BYOD.